PERMAINAN RICIKAN KENONG DALAM KARAWITAN JAWA GAYA SURAKARTA - Djoko Purwanto (Gelar : Jurnal Seni Budaya, 2013)
Kenong is one of structural ricikan, along with other ricikans such as kethuk, kempul, and gong,fill–in reciprocally guiding and creating the tradition of gending karawitan forms Surakartan style.This study will not elaborate the making of kenong with good quality, instead, it will elaborate theperforming techniques in Javanese karawitan. The studies that been done in libraries in IndonesiaArt Institute of Surakarta (Central Library, Karawitan Department Library, Post Graduate Library)and personal collections, also audio record collections that been sold commercially or been keptas personal properties had elaborated several ricikan kenong’s performing techniques. The resultof the study, according to Djojomlojo, kenong performing techniques using terms such as tunggalrasa, kempyung, salah gumun, tuturan, plesetan, goyang, kerepan, ngganter, and nitir. Theperforming or knocking techniques applied in Javanese karawitan, but it is not performed in onesingle gending. Instead, they are performed in some separates gending. Besides, there are twokenong performing techniques that are not categorized on the previous. They are (1) performingtechnique in gending Loro–loro Topeng; (2) kenong performing technique in gending palaran.Through understanding and learning several kenong performing techniques, we will find the morekomprehensive karawitan aesthetic in Javanese tradition karawitan surakarta style.